Characteristics of laser-induced plasma under reduced background pressure with Doppler spectroscopy of excited atomic species near the shockwave front. (March 2018) - Dojić, Dejan; Skočić, Miloš; Bukvić, Srdjan
Highlights: We present elliptical shape of Copper spectral lines found in LIBS. We demonstrate that the elliptical shape is due to Doppler Effect. Relying on Doppler Effect we estimate expansion speed in several gases. We found that spectral line intensity is linearly increasing with pressure of surrounding gas. Graphical abstract: Abstract: We present measurements of Laser Induced Plasma expansion relying on classical, laterally resolved spectroscopy. Easy observable Doppler splitting of Cu I 324.75 nm spectral line provides measurement of radial expansion velocity in a straightforward way. The measurements are conducted in atmosphere of air, argon and hydrogen at low pressure in the range 20–200 Pa. We found that expansion velocity is linearly decreasing if pressure of surrounding gas increases, with velocity/pressure slope nearly the same for all three gases. Copper atoms have the highest expansion speed in argon ( ∼ 50 km/s) and the smallest speed in air ( ∼ 42 km/s). It is found that expansion velocity increases linearly with irradiance, while intensity of the spectral line is quite insensitive to the laser irradiance.